2013
DOI: 10.1017/s1041610213000860
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic interventions for community-dwelling people with dementia and their family caregivers: a systematic review

Abstract: Background:In this review, we study the effects of dyadic psychosocial interventions focused on communitydwelling people with dementia and their family caregivers, and the relationship of the effects with intervention components of programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 65 publications
(46 reference statements)
3
168
2
3
Order By: Relevance
“…A review of dyadic caregiver interventions for people living with dementia in the community; six (806 participants) of the eight studies (1,015 participants) did not demonstrate a statistically significant improvement in BPSD ( Van't Leven et al, 2013). A review of reminiscence therapy was included as the highest quality review of recreational interventions identified (Woods et al, 2005).…”
Section: Effects Of Interventions For Bpsdmentioning
confidence: 99%
“…A review of dyadic caregiver interventions for people living with dementia in the community; six (806 participants) of the eight studies (1,015 participants) did not demonstrate a statistically significant improvement in BPSD ( Van't Leven et al, 2013). A review of reminiscence therapy was included as the highest quality review of recreational interventions identified (Woods et al, 2005).…”
Section: Effects Of Interventions For Bpsdmentioning
confidence: 99%
“…Van't Leven et al (2013) found that studies only found significant benefit when a specific aspect of functioning was focused upon, and Regan's (2013) review of 15 studies found that modified cognitive behavioural therapy had some efficacy in improving mood. Finally an RCT of couple reminiscence (Woods, Aguirre, Spector & Orrell, 2012) failed to show benefit for those with dementia or their carers, though it was suggested from a compliance analysis that there were benefits for people with dementia alongside raised anxiety for carers.…”
Section: Interventions For People With Dementia Living In the Communitymentioning
confidence: 99%
“…Most people with dementia live at home and are cared for by informal caregivers, mostly spouses and children, who play a crucial role in the supervision and therapy because of the progressive mental decline of the disease. Knowing that on the one hand there is a high cost of the disease for the society due to frequent hospitalization and permanent institutionalization in nursing homes and, on the other hand, people with dementia prefer to remain in their trusted environment as long as possible, it can be stated that informal caregivers are probably cost saving for society, but also essential in the care process [1][2][3][4][5][6][7][8][9]. Especially given the emerging focus on person-centered care, caregivers are indispensable to maximize well-being of people with dementia since they are best placed to identify their unique needs and desires [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although caregiving for a loved one can be very satisfying, it also demands a lot from informal caregivers over long periods [5,11]. Most research in the past decade has shown that informal caregivers have more health problems, visit healthcare professionals more frequently, suffer from isolation, and have an increased risk of depression, distress, and other illness [1,2,6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%